2014
DOI: 10.1007/s00404-014-3552-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ovarian function and metabolic factors in women affected by polycystic ovary syndrome after treatment with d-Chiro-Inositol

Abstract: D-Chiro-Inositol is effective in improving ovarian function and metabolism of patients affected by PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 59 publications
1
42
0
4
Order By: Relevance
“…In our previous study [1], even if all the recruited patients were lean, we reported 5.38 ± 1.54 as mean glycaemia/IRI ratio and 3.44 ± 1.18 as mean HOMA (Homeostasis Model Assessment) index, so we evidenced insulin resistance/hyperglycaemia (HOMA C 2.5) in the enrolled population. Moreover, none of these patients had diabetic relatives (first or second degree).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In our previous study [1], even if all the recruited patients were lean, we reported 5.38 ± 1.54 as mean glycaemia/IRI ratio and 3.44 ± 1.18 as mean HOMA (Homeostasis Model Assessment) index, so we evidenced insulin resistance/hyperglycaemia (HOMA C 2.5) in the enrolled population. Moreover, none of these patients had diabetic relatives (first or second degree).…”
mentioning
confidence: 72%
“…We appreciate Vitagliano and Colleagues' interest in our recent article [1] about ovarian function and metabolic factors in women affected by polycystic ovary syndrome (PCOS) after treatment with D-chiro-inositol. We are grateful for their insightful comments [2] and the opportunity to clarify a number of elements from our work.…”
Section: Dear Editormentioning
confidence: 97%
“…[132] The treatment of 48 patients affected by PCOS and menstrual irregularities with D-chiro-inositol and folic acid resulted in statistically significant improvements in several measures of ovarian function and metabolic function. [133] In PCOS sufferers metformin increases the insulin-stimulated release of the putative D-chiroinositol-containing phosphoglycan that mediates insulin action: [134] there is a selective impairment in PCOS sufferers between insulin action and the release of the mediator. [135] PCOS has been associated with a degree of oxidative stress: the administration of D-chiroinositol to PCOS sufferers prevents the oxidation of protein thiol groups in the follicular fluid.…”
Section: D-chiro-inositol Diabetes Pregnancy and Polycystic Ovary Smentioning
confidence: 99%
“…1) (References in Table 1: Costantino et al, 2009[13]; Genazzani et al, 2014[27]; Genazzani et al, 2008[25]; Nestler et al, 1999[48]; Genazzani et al, 2014[26]; Laganà et al, 2015[39]; Nordio and Proietti, 2012[49]; Pizzo et al, 2014[60]).…”
Section: Nutrients and Pcosmentioning
confidence: 99%